2017
DOI: 10.1111/myc.12646
|View full text |Cite
|
Sign up to set email alerts
|

Invasive fungal infection following chemotherapy for acute myeloid leukaemia—Experience from a developing country

Abstract: The incidence of invasive fungal infections (IFI) is believed to be higher in patients with acute myeloid leukaemia (AML) undergoing chemotherapy in non-HEPA-filtered rooms. The aim of this study is to review the incidence of IFI in a large cohort of patients with AML treated at a single centre in India. Two hundred and twenty-two patients with AML treated with either induction chemotherapy or salvage chemotherapy between 2008 and 2013 were studied retrospectively. IFI was defined as per the revised EORTC-MSG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
(36 reference statements)
2
16
0
Order By: Relevance
“…Like other studies from India, diabetes stands apart as the single most important risk factor for developing mucormycosis in our study in contrast to data from the developed countries, where haematological malignancies predominate . Outcomes of mucormycosis from haematology patients are infrequently reported in low middle income countries due to the lack of diagnostic and treatment facilities . In our study, patients with haematological conditions were typically younger with male predominance.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…Like other studies from India, diabetes stands apart as the single most important risk factor for developing mucormycosis in our study in contrast to data from the developed countries, where haematological malignancies predominate . Outcomes of mucormycosis from haematology patients are infrequently reported in low middle income countries due to the lack of diagnostic and treatment facilities . In our study, patients with haematological conditions were typically younger with male predominance.…”
Section: Discussionsupporting
confidence: 45%
“…F I G U R E 3 Details the treatment details of the patients involved in the study from haematology patients are infrequently reported in low middle income countries due to the lack of diagnostic and treatment facilities. 12 In our study, patients with haematological conditions were typically younger with male predominance. Unlike developed countries were pulmonary mucormycosis is the commonest presentation in patients with haematological malignancies, invasive fungal sinusitis is the commonest clinical presentation in our setting.…”
Section: Apophysomyces Elegansmentioning
confidence: 57%
See 3 more Smart Citations